Topical Corticosteroids Utilisation and Cost Variation in Dermatology Outpatient of a Tertiary Hospital in Kathmandu - Shrestha, Deepti; Joshi, Smita; Shakya Gurung, Rashmi; Poudel, Rekha; Upreti, Anup R (Journal of Institute of Medicine Nepal, 2021)
Introduction Topical corticosteroids (TCs) are one of the important drugs prescribed in skin diseases. Cost is an important factor for compliance to treatment. Cost analysis provides the variation of costs which helps in economic benefit in the use of drugs. Thus the aim of the study was to assess the TC utilisation in Dermatology department and study its cost variation. Methods A descriptive cross-sectional study was conducted in the out-patient of Department of Dermatology, Nepal Medical College Teaching Hospital. Patient demographic, disease, name of topical steroid, vehicle, strength, single or combination, cost of the different brands of TCs were analysed. Results Out of 216 patients, 109 (50.5%) were females and 67 (31%) were of 21-30 years age group . Dermatitis was the most common skin condition encountered (106, 49.1%). Most common TC prescribed as single therapy was mometasone furoate 0.1%, (51, 23.6%) and betamethasone valerate 0.1% with fusidic acid, (48, 22.2%) as combination therapy. Mometasone furoate 0.1% cream, (15 gm) showed the maximum cost variation (94.7%) in single drug product while clobetasol propionate 0.05% with salicylic acid ointment (20gm) showed the maximum cost variation (95.55%) in a combination product. Conclusion In Dermatology outpatient, the commonest indication of TCs use during our study was dermatitis, with commonest TCs prescribed being mometasone furoate. Cream was the most favoured vehicle. Cost variation was as high as 95%. Reduction in this cost variation would ease the financial burden on patients which will help in improving the patient compliance in a resource limited population.